The Influence of Program Effectiveness on the Sustainability of the Farmer Food Corporation (KPP) Business at PT. XYZ - Widi, Riantin Hikmah; Karyani, Tuti; Hapsari, Hepi; Trimo, Lucyana (Agro Bali : Agricultural Journal, 2024)
PT. XYZ is one of the Farmer Food Corporations (KPP) in Ciamis Regency, providing services ranging from production facilities to facilitating credit capital applications. This farmer corporatization program benefits farmers by increasing their income, thus necessitating the sustainability of PT. XYZ. Therefore, it is crucial to examine the effectiveness of the PT. XYZ program, its sustainability level, and the impact of its effectiveness on business sustainability. This study employs an integrated (mixed method) approach with a dominant quantitative design. The population comprises rice farmers who are members of the Farmer Food Corporation in Ciamis Regency under PT. XYZ. A sample size of 51 respondents was selected using a simple random sampling method to ensure equal representation. The effectiveness of the PT. XYZ program was analyzed descriptively through a descriptive statistical analysis approach, and the Partial Least Square (PLS) Structural Equation Model (SEM) analysis was performed to understand the influence of program effectiveness on PT. XYZ's business sustainability. The research results indicate that all variables influence the effectiveness of the PT. XYZ programs are constructed by real manifests, with contributions ranging from medium to high. The five manifest variables constructing effectiveness are program objectives, real change, program socialization, precision, and monitoring. The sustainability variable is constructed by market, workplace, environment, and community variables. The program's effectiveness has a significant influence on PT. XYZ's business sustainability. In conclusion, the PT. XYZ program effectively enhances farmers' income and contributes significantly to the sustainability of PT. XYZ's business. Continuous improvement in program implementation and monitoring is essential to maintain and enhance these benefits.